AB0762 Biological therapy for large vessel vasculitis: A systematic review. (23rd January 2014) - Silva, L.; Blanco, R.; Martínez-Taboada, V.; Loza, E.; Rúa-Figueroa, I.; Muñoz-Fernández, S.; Pego, J.M.
Abstract : Background: Treatment of large-vessel vasculitis (LVV) is mainly based on high doses of corticosteroids (CS). There is controversy on the use of methotrexate and azathioprine as steroid-sparing. Cytokines like IL-6 or TNF could play an important role in the pathogenesis of LVV, thus could be targets in the treatment of LVV patients. Objectives: To systematically review the efficacy and safety of biological agents in the treatment of LVV. Methods: We systematically searched MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials up to October 2011 using a comprehensive search strategy for giant cell arteritis (GCA), Takayasu's arteritis (TA), biologic agents, efficacy and safety (mesh terms and text words). Selection criteria were predefined by protocol. We selected meta-analysis, systematic literature reviews, clinical trials (CT), cohort studies and case series with >3 cases, that included >18 year-old patients with GCA or TA on biologic drugs. Studies including patients with Behçet disease, cryoglobulinemia, ANCA associated vasculitis, secondary vasculitis, and basic science studies were excluded. Title and abstract selection and subsequent detailed review of selected articles were independently performed by two reviewers. The included studies quality was graded using the Oxford Levels of Evidence Scale, and results expressed as level of evidence (LE), recommendation grade (RG). Results: The search strategy identified 2762 potentially relevant articles, of which 80 were selected for full paper review. Finally, 3 were included in the analysis and 3 were found by handsearch. We included 2 randomized CT and 4 case series, which accounted for 112 patients. Main characteristics and results of the included studies are shown in the table. Conclusions: Infliximab is not more effective than CS in the induction of remission of CGA patients (LE 1b; GR A) but could be effective (remission induction, CS sparing) in CS-refractory TA (LE 4; GR C). Etanercept has a role as steroid-sparing agent in GCA with CS related severe adverse events (LE 1b; GR A) and could be effective (remission induction, CS sparing) in CS-refractory TA (LE 4; GR C). Tocilizumab might be effective (remission induction, CS sparing) in LVV (LE 4; GR C). Disclosure of Interest: None Declared